Los delitos de aborto e infanticidio en Antioquia, 1890-1930 (2009)
ABSTRACT: This article explores the perceptions of female sexuality and their relation-ship with the social codes of honor prevalent in Antioquia between 1890 and 1930, based on the examination of 97 cases of abortion and infanticide, taken from the Archivo Histórico Judicial of Medellín. It identifies the peculiarities that defined those crimes as punishable, visualizing how they were judged and controlled depending on the defendant’s marital state and “fame” within society. Furthermore, it examines the dificulties that the judicial powers had to prove crimes of abortion and infanticide, due in large part to the lack of gynecological and obstetric knowledge and the way in which the application of the law was subordinate to moral and religious criteria which, in practice, mixed and interfered with the interpretation and application of legal provisions.